Assessing the antimicrobial properties of copper-iodide doped adhesives in an In vitro caries model: A pilot study - Anthony S Mennito; Michael Schmidt; Andrew Lane; Abigail Kelly; Camila Sabatini; Walter Renne; Zachary Evans (Wolters Kluwer Medknow Publications, 2022)
Context: Recurrent caries are the leading cause of composite resin failure. Aims: The purpose of this pilot study was to test the efficacy of a novel copper iodide (CuI) containing dental adhesive in an in vitro caries model. Subjects and Methods: Streptococcus mutans and Lactobacillus acidophilus were grown individually on the complex medium for 48 h at 37°C. The pH of the mixed medium was 7.0 initially and tested every 24 h. 40 extracted teeth were prepared with standardized cavity preparations and coated with control or experimental CuI adhesives and imaged using a micro-computed tomography (microCT). Four study groups were evaluated: (1) control (2) 0.5 μg/ml CuI (3) 1.0 μg/ml CuI, 4) 5.0 μg/ml CuI. After incubation, the teeth were re-imaged using the microCT. Utilizing AnalyzePro software the three-dimensional data sets were overlaid and demineralization was measured and statistics were run. Statistics: Stratified ANOVA models were run to determine if there were differences between the control and experimental adhesive groups. Similarly, pH and bacterial concentrations were evaluated to ensure the viability of polymicrobial specimen. Results and Conclusions: Significant differences were found between the control group and the 1.0 and 5.0 CuI adhesive groups. No differences in pH were noted between the groups. Overlaid changes in demineralization were recorded as volume loss. CuI adhesives with 5 mg/ml or higher have the potential to limit tooth demineralization after bacterial penetration of a dental restoration in an in vitro caries model. Further testing is needed.